Higher education in the global quarantine: Disruptions and transitions - Canaza-Choque, Franklin Américo (2020)
This work analyzes some of the preliminary implications that the COVID-19 pandemic has had in Higher Education. Faced with the panorama of global repression and immediate impacts, different Higher Education Institutions decided to adopt distance education. The same that has not only led to re-inventing teaching and reorganizing the teaching-learning process. But besides, it also deepened the gap and the real structural conditions of a disadvantaged student population. Consequently, it is doubly meritorious to strengthen a distance education that does not only include the mere participation of the training institutions themselves. On the contrary, given the extraordinary situation, it will be necessary for the different levels of government to intervene in order to redouble efforts in educational measures, programs and policies that effectively guarantee the right to distance learning at this level of education.